Process Evaluation of the Implementation of the Secondary 2 Program of Project P.A.T.H.S. in the Experimental Implementation Phase - Daniel T. L. Shek; Tak Yan Lee; Rachel C. F. Sun (The Scientific World Journal)
This study aimed to understand the implementation quality of the Tier 1 Program (Secondary 2 Curriculum) delivered in the Experimental Implementation Phase of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes). Observers carried out process evaluation in the form of systematic observations of curriculum units in four randomly selected schools. Results showed that the overall level of program adherence was generally high, ranging from 70 to 95%, with an average of 83.6%. The mean ratings of the program implementation quality were high, and the inter-rater reliability on these ratings across the observers was highly reliable. Despite limitations, the findings of this study suggest that the implementation quality of the Secondary 2 Program (Tier 1 Program) of the Experimental Implementation Phase was favorable, and provide supporting evidence to account for the successful and encouraging outcomes of a major positive youth development program in Hong Kong.